IS/IT STRATEGIC PLANNING PADA SMK MUHAMMADIYAH 1 PURWOKERTO DENGAN METODE WARD & PEPPARD - Fiby Nur Afiana; Ito Setiawan; Ilham Arjun Banomo (CESS (Journal of Computer Engineering, System and Science), 2019)
This study aims to design strategic information systems and information technology (SI / IT) planning at Muhammadiyah 1 Purwokerto Vocational School using the Ward & Peppard method. With the increasing number of vocational schools in Banyumas, competition between schools, especially the private sector, is inevitable. One form of competition is by utilizing technology, technological developments in the world of education when not only as support but also as an enabler for the organization's business processes. To be able to compete in schools must have the right strategy by utilizing technology as a supporting tool to improve quality and quality. IS / IT strategic planning is a process of finding, collecting, researching a portfolio of technology-based SI applications that will support business processes and create the main objectives of an organization / company business. SI / IT also affects business processes to determine the strategic steps used in the strategic planning of the organization / company. IS / IT Strategic Planning Research at Muhammadiyah 1 Purwokerto Vocational School with Ward & Peppard will produce an IS / IT strategic planning proposal in the form of IT strategy (Information Technology), SI strategy (Information System), and IS / IT management strategy in document form. SI / IT solutions are generated to support the main business processes of Muhammadiyah 1 Purwokerto Vocational School in the form of application portfolio recommendations in the future.